2020
DOI: 10.1111/jorc.12345
|View full text |Cite
|
Sign up to set email alerts
|

Care Needs for Organ Transplant Recipients Scale: Development and psychometric testing

Abstract: Background Needs assessment can determine how large the gap is between needs and available services; however, no tools are available to assess the unmet needs of renal transplant recipients. Objectives The aim of this study was to develop the Care Needs for Organ Transplant Recipients Scale (CNOTRS) and examine its psychometric properties. Design A cross‐sectional design for instrument development and psychometric testing. Participants In total, 217 renal transplant recipients were recruited through convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Future studies should recruit more participants to verify the reliability of the depression subscale of the HADS among transplant recipients. Fourth, the CNOTRS, as the instrument for measuring recipients’ unmet care needs in this study, exhibited satisfactory reliability and validity through meticulous psychometric properties testing when used to assess kidney transplant recipients in the original study (Chang et al, 2020). Our study is the first to use the CNOTRS to measure the unmet care needs in liver transplantation recipients (Cronbach’s α 0.91) and the recipients’ spouses (Cronbach’s α 0.94) showing good internal consistency.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Future studies should recruit more participants to verify the reliability of the depression subscale of the HADS among transplant recipients. Fourth, the CNOTRS, as the instrument for measuring recipients’ unmet care needs in this study, exhibited satisfactory reliability and validity through meticulous psychometric properties testing when used to assess kidney transplant recipients in the original study (Chang et al, 2020). Our study is the first to use the CNOTRS to measure the unmet care needs in liver transplantation recipients (Cronbach’s α 0.91) and the recipients’ spouses (Cronbach’s α 0.94) showing good internal consistency.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with the previous study (Rodrigue et al, 2011), we found that spouses need to assist recipients in facing the psychological distress of transplantation; the concern of disease recurrence (Q3) and uncertainty about the future (Q4) are especially burdensome concerns. Recipients who experienced organ rejection and complications within 6 months of transplantation reported having high anxiety and depression (Chang et al, 2020); the occurrence of complications related to transplantation such as severe infection (Bourlon et al, 2020), malignancies (Bardou et al, 2019), and rejection (Bardou et al, 2019) is the greatest challenge in posttransplant care. To decrease psychological unmet needs and levels of anxiety and depression among recipients and spouses, health care providers must instruct them in self-management skills, common complications after transplantation, and recognizing early signs and symptoms of complications (Been-Dahmen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations